Vietnam: chronicle of a war - Cronkite, Walter; CBS News.; CBS Video (Firm); Fox Video (Firm) (Beverly Hills, Calif. : CBS/Fox Video, 1984)
Drawing upon the resources of the CBS News Archives, this program traces the history of the devastating conflict.
Narrated by Walter Cronkite ; with correspondents: Ed Bradley, Charles Collingwood, Bruce Dunning, Charles Kuralt, Dan Rather, Eric Sevareid, Mike Wallace.
VHS. Hi-fi.
Keywords: Vietnamese Conflict, 1961-1975.